Pattern of Medicolegal Ocular Trauma in Cases of Assault and Its Visual Outcome in An Outpatient Department of a Tertiary Care Hospital: Doi: 10.36351/pjo.v40i3.1778 - Fasih, Uzma; Shahid, Erum (Pakistan Journal of Ophthalmology, 2024)
Purpose: To determine the pattern of medicolegalocular traumaand its visual outcome in cases of assault presenting in the outpatient department of ophthalmology. Study Design: Descriptive cross-sectional study. Place and Duration of Study: Abbasi Shaheed Hospital, Karachi Medical and dental college (KMDC), from January, 2020 to June, 2022. Methods: This study included 199 patients of assault, registered as medicolegal cases and referred for examination by a police surgeon.Findings were recorded on a pre designed proforma and categorised according to Bermingham Eye Trauma Terminology (BETT). The results were presented in frequencies. Results: The study analyzed ocular injuries in a group of participants, predominantly male (81.9%), with a mean age of 34 years. The majority of injuries were closed-globe (70.4%), primarily occurring in Zone 1. Pre-treatment visual acuity was generally high, with 85.4% of patients having 20/20-20/40 vision, which improved slightly to 87.4% post-treatment. Open-globe injuries were rare (1.0%) and also confined to Zone 1. The most common trauma setting was the home, and the most frequent cause of injury was assault using a fist. Conclusion: Majority of the patients were young males who suffered trauma at home and fist was the most common causative agent. The study highlights the prevalence of closed-globe injuries, the effectiveness of treatment in preserving visual acuity, and the domestic nature of most ocular traumas.